Ibuprofen Can Induce Syndrome of Inappropriate Diuresis in Healthy Young Patients - Céline Roche; Céline Ragot; Jean-Luc Moalic; Fabrice Simon; Manuela Oliver (Case Reports in Medicine)
A 30-year-old caucasian woman, without past medical history or known drug use, was admitted to the emergency department for persistent fever and arthralgias. The laboratory analysis showed moderate hypoosmolar hyponatremia (Na: 132 mmol/L, osmolality: 239 mOsm/L), normal sodium excretion (<20 mmol/L), and a high urinary osmolality (415 mOsm/L). Later, she deteriorated with seizures and deeper hyponatremia (Na: 113 mmol/L) and so was moved to the critical care unit. At first, no obvious aetiology was found, the patient was euvolemic, as she was well hydrated and lacked concerning findings of heart failure, renal disease, or liver cirrhosis. A syndrome of inappropriate diuresis (SIAD) was proposed, and corrective measures were started immediately to reduce her hyponatremia, including restriction of fluid intake. The administration of intravenous hypertonic saline solution permitted normal neurological status to be restored and corrected the sodium concentration but induced reversible acute renal failure. Further investigation revealed that the patient had ingested 8 g ibuprofen two days before admission. After other aetiologies were ruled out, drug-induced SIAD due to ibuprofen was the most likely diagnosis for this patient. SIAD-associated hyponatremia and acute renal failure are rare side effects of nonsteroidal anti-inflammatory drugs, particularly in young people. Therefore, this case may represent a unique case of NSAID-induced SIAD and highlight the need to obtain thorough medication histories and exclude all other potential causes in hyponatremic patients.